Development of High Performance Sulfonated Poly (Ether Ether Ketone) Based Composite Proton Exchange Membranes - Chia, Min Yan (2019)
Increasing demand of energy and the depletion of non-renewable fossil fuels had instigated the search for alternative sources of energy. Direct methanol fuel cell (DMFC) becomes a very interesting research theme, especially its proton exchange membrane. In this study, attempt to replace the costly Nafion based proton exchange membrane with a new material was done. A low cost polymer, poly ether ether ketone (PEEK) was sulfonated into SPEEK. Additives (silicotungstic acid supported on silica, SiO2-SiWA) were incorporated into the polymer matrix. In order to enhance the stability, performance and homogeneity of the membrane, various modifications, including ultrasonic treatment and addition of coupling agents were tested. From the results, ultrasonic treatment provided extra energy through its cavitation effect, thereby stabilised SiO2-SiWA in the membrane. It was also found that silica:SiWA weight ratio of 2:1 could improve the immobilisation effect of silica on SiWA. Addition of aminopropyl triethoxysilane (APTES) and carbonyl diimidazole (CDI) as coupling agent and promoter further improved the compatibility between organic polymer and inorganic additives, where it showed higher selectivity (10.6 × 104 S.s/cm3) than Nafion membrane. This was achieved through the successful bridging of organic SPEEK andinorganic silica by a series of chemical reactions involving APTES and CDI. As APTES and CDI were able to improve the performance of SPEEK/SiO2-SiWA composite membrane, the composition was tested by using alumina and iron (III) oxide as support for SiWA. However, due to their amphoteric nature and incompatibility with silane coupling agents, there was no positive outcome. In conclusion, a SPEEK/SiO2-SiWA composite membrane with 10 wt% of silica and 5 wt% of silicotungstic acid provided the best performance, with the utilisation of ultrasonic treatment to improve dispersion and stability. At the same time, APTES and CDI acted as coupling agent and promoter respectively further enhanced the performance of the membrane. This laid a foundation for future research on SPEEK based membrane development as a continuous effort to replace costly Nafion membrane.